Epidemiological features and risk factors of human psittacosis in Hangzhou City, eastern China - Zhou Sun; Ke Xu; Liangliang Huo; Xingliang Zhang; Yi Wang; Yonghui Gong; Bingbing Chen (Frontiers in Public Health)
ObjectivesThis study aimed to investigate the epidemiological characteristics and risk factors associated with human psittacosis in Hangzhou city, eastern China.MethodsThe human psittacosis data from 2021 to 2024 were obtained from the China information system for diseases control and prevention infectious disease surveillance system. Epidemiological investigations were carried out on the patients' past medical history, clinical manifestations, chest CT results and treatment status. A community-based 1:3 matched case-control study was performed to investigate the risk factors associated with Chlamydia psittaci infection.ResultsDuring the study period, 137 confirmed cases of human psittacosis were identified through laboratory tests, of which 24 (17.52%) were classified as critical cases, including one fatality. The epidemic curve indicated that the majority of cases occurred between October and March. Among the cases, 48.91% were female, and the median age was 63 years. There were more female cases among those aged <60 years, while there were more male cases among those aged ≥60 years. Multivariate logistic regression analysis revealed that the presence of bird habitats within 500 m of the living area [odds ratio (OR) = 3.81, 95% confidence interval (CI) = 2.19–6.61], parrots kept (OR = 2.95, 95%CI = 1.10–7.89) and poultry kept (OR = 2.15, 95%CI = 1.02–4.53) remained significantly associated with the risk of disease infection.ConclusionsHuman psittacosis has become a notable public health concern in Hangzhou city, with an increase in psittacosis cases reported in recent years. Exposure to poultry, birds, or environments contaminated with Chlamydia psittaci was associated with infection. Urgent actions to reduce psittacosis cases and mitigate the impact of outbreaks are needed, including strengthening surveillance, raising public awareness, and promoting collaboration between the agricultural and health sectors.